2019
DOI: 10.3390/cancers11010114
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Proteolytic Enzymes by Small Cell Lung Cancer Circulating Tumor Cell Lines

Abstract: Small cell lung cancer (SCLC) is an aggressive type of lung cancer which disseminates vigorously and has a dismal prognosis. Metastasis of SCLC is linked to an extremely high number of circulating tumor cells (CTCs), which form chemoresistant spheroids, termed tumorospheres. Intravasation and extravasation during tumor spread requires the activity of a number of proteases to disintegrate the stroma and vascular tissue. Generation of several permanent SCLC CTC lines allowed us to screen for the expression of 35… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 87 publications
0
24
0
Order By: Relevance
“… 2013 ; Newby 2008 ; Rath et al. 2019 ) thus helping tumour invasion. We considered this modelling and computational approach since in the experimental literature there is still little knowledge about the directional interactions of macrophages with the directional/random ECM architecture, and how this affects tumour spread.…”
Section: Discussionmentioning
confidence: 99%
“… 2013 ; Newby 2008 ; Rath et al. 2019 ) thus helping tumour invasion. We considered this modelling and computational approach since in the experimental literature there is still little knowledge about the directional interactions of macrophages with the directional/random ECM architecture, and how this affects tumour spread.…”
Section: Discussionmentioning
confidence: 99%
“…CTSS proteolytic degradation of nidogen-1, an essential component of the basement membrane and a substrate of CTSS, is strongly associated with non-small cell lung cancer [131]. A recent study showed an increased and exclusive secretion of CTSS in circulating tumor cells of small cell lung cancer, which may predict distant metastasis and targeting CTSS may limit tumor dissemination to distal sites [132]. Interestingly, CTSS has also been linked to breast-to-brain metastasis via processing of the junctional adhesion molecule-B and subsequent blood-brain barrier transmigration [75].…”
Section: Lung Cancermentioning
confidence: 99%
“…Several groups have demonstrated that CTCs can be cultured, notably from breast and prostate cancer patients (e.g., Zhang et al, 2013;Yu et al, 2014;Kolostova et al, 2014), with potential for real-time drug testing to predict donor patient responses with robust assays tailored to low cell numbers (Figure 1). CTC cell lines can also be derived, notably from patients with breast, colorectal, and gastric cancers, and with SCLC (Yu et al, 2014;Rath et al, 2019, Brungs et al, 2020Soler et al, 2018;Klameth et al, 2017) adding new tools for drug development and to explore the biology of advanced cancers, with the caveat, as with all cell cul-tures, that long-term passage on plastic is likely to result in irreversible adaptation and clonal outgrowth. CTCs have also been used to generate patient CTC Derived eXplant (CDX) models in mice, first shown for CTCs in breast cancer patients (Baccelli et al, 2013) and subsequently in SCLC where CDX models reproduce the donor patient's response to standard-of-care chemotherapy (Hodgkinson et al, 2014;Drapkin et al, 2018, Figure 1).…”
Section: Predicting Therapy Responses With Ctcsmentioning
confidence: 99%